Peran Abdoel Moeis di Balik Karakterisasi Tokoh-Tokoh Novel Salah Asuhan Negosiasi sebagai Gambaran Kondisi Kebangsaan - Sari, Reno Wulan (Puitika, 2020)
Indonesian literary history leads us to the world of Indonesian history when various nations work being an imaginative history-recording of all events, including perpetuating human journey of a different era. The historical records written by the author to give the picture of the human condition when the work is born. This brings the reader to an understanding of the reader on a journey of human life, the times, and the nation. Call it the works that carries shades of the colonial period on the works of Balai Pustaka, Propaganda Japan, until the readings are categorized as illegal. In essence, the work will be the theme of the struggle of the Indonesian people through a variety of ways that can be seen as a tactic to anticipate the emergence of nationalism author and strengthen national identity, such as contained in the novel One Care Abdoel Moeis work. Indeed, One Care is not just a load of indigenous issues, romance, and cultural differences, but also carry the spirit of the author to lead to a love of the Indonesian nation, addressed to readers. One of the Children born as a form of literature that carries two goals, adhere to requirements aimed at Balai Pustaka in order to be legal work, but still carries the spirit of nationalism to build the nation's character to readers. This is the form of negotiations conducted through characterization Abdoel Moes fictional characters in his work.Â